GaN microstructure light-emitting diodes directly fabricated on tungsten-metal electrodes using a micro-patterned graphene interlayer. (June 2019) - Chung, Kunook; Lee, Keundong; Tchoe, Youngbin; Oh, Hongseok; Park, JunBeom; Hyun, Jerome K.; Yi, Gyu-Chul
Abstract: We report on the selective-area growth of GaN microstructures on tungsten (W)-metal electrodes using a micro-patterned graphene intermediate layer between GaN and W, and demonstrate their use as light-emitting diodes (LEDs). Prior to the GaN growths, the cm-scale graphene layer was transferred on W and then further patterned into a regular array of few-μm-sized graphene microdots using conventional lithography. The graphene microdots served as a seed layer for selectively growing crack-free GaN microstructures with regular diameter and spacing. Each microstructure displayed a microdisk morphology, exhibiting a single crystalline phase from epitaxial lateral overgrowth (ELOG). We observed ohmic behavior between the as-grown GaN microdisks and underlying W film, facilitating the fabrication of LED microarrays. Using the underlying W layer as an ohmic contact, we fabricated p-n junction GaN microdisk LEDs, consisting of three periods of Inx Ga1–x N/GaN multiple quantum wells. Uniform electroluminescence was observed across the microdisks. These results open up novel strategies for streamlined fabrication of high-performance and high-resolution LEDs. Graphical abstract: Image 1 Highlights: Position-controlled GaN microdisk LEDs were directly fabricated on W electrodes with a micro-patterned graphene seed layer. Graphene on W served as a seed layer for selectively growing crack-free GaN microdisk. Ohmic behavior between the as-grown GaN microdisk and underlying W film was observed. Stable and uniform electroluminescence was observed across the GaN microdisk LEDs.